Angiopathy in Rheumatoid Arthritis - Ergasheva Ma’mura Tashtemirovna; Yarmukhamedova Saodat Khabibovna; Khusainova Munira Alisherovna; Khaydarova Zarrina Erkinovna (Miasto Przyszłości, 2023)
Relevance. Among all rheumatological diseases, rheumatoid arthritis (RA) accounts for 3% of cases, and the number of such patients is growing. RA is characterized by systemic vascular lesion (angiopathy), characterized by the international Chapel Hill classification as "vasculitis associated with a systemic disease". The purpose of the work: to improve the quality of diagnosis, to establish new links in pathogenesis and to identify prognostic criteria for the course of vascular lesions in RA. Materials and methods. 131 RA patients were under observation. The ratio of men and women was 1: 2, the minimum, moderate and high degrees of disease activity were 1: 2: 1, respectively, the average age of the examined patients was 45.70 ± 1.02 years, the duration of clinical manifestation was 9.40 ± 0.68 years, stages I, II, III and IV were diagnosed in 8, 40, 34 and 19% of the number of patients, respectively. Echocardiography, sonography and ultrasound dopplerography of vessels, biomicroscopy were performed conjunctiva, morphological examination of nephrobiopaths, determined integral indices of clinical and instrumental vascular pathology. Results. Systemic angiopathy was observed in 61%of RA patients, more often in cases of high activity in the presence of osteoporosis, while the development of skin vasculitis and peripheral vasoneuropathy was closely related to the level of antibodies to cyclic citrulline peptide in the blood serum, which, along with the concentration of C-reactive protein, has negative prognostic significance for vascular pathology. Appearance digital arteritis is determined by the activity of articular syndrome, glomerulonephritis — a high content of circulating immune complexes in the blood, and the presence of angiopathy reflects an increase in pressure in the small circle of blood circulation. Conclusions. Patients with RA develop mesangioproliferative or mesangiocapillary glomerulonephritis in a ratio of 2: 1 with a regular tubulointerstitialcomponent and a deposit of immunoglobulins and complement components (in stroma → glomeruli → tubules → vessels), while structural changes in renal vessels are closely related to clinical and instrumental manifestations of systemic rheumatoid angiopathy. Blood counts of C-reactive protein are more than 25 mg/l and anti-citrulline antibodies over 40 E/ml are predictive criteria for systemic vascular pathology and damage to the renal stroma, and severe changes in the renal tubules are risk factors for high rates of progression of articular syndrome.